(3MbGFb GdJChjd aj eJTGHg GdJfRjds - (3GdQVj, GdYdhqj, GdMSjfj, GdehShj, CHh GdMSf, GdnqTpQja GdpqQVi, eMeO Hf GdMSjf Hf ehSi, J(B406(3g`s
(3ChdgG (B:s
(3GdShQI GdJj jPcQ ajgG Bd YeQGf, eSCdI hef SCd Yf eYfi bhdg JYGdi (B{(3gh GdPj CfRd Ydjc GdcJGH efg BjGJ eMceGJ gf Ce GdcJGH hCNQ eJTGHgGJ(B}...s
(3BNQgG (B:s
(3hBNQg aj GdcdGe Ydi bhdg JYGdi (B{(3Ef Gddg dG jZaQ Cf jTQc Hg (B...}(3,bhdg(B:(3heG Sei Gddg SHMGfg GdfUGQi eTQcjf EdG aj BjI hGMOI (B...(3aCLQi SHMGfg Ydjge GSe GdTQc ceG CLQi Ydjge GSe GdcaQ(B...s
(3HChd GdfSNI agQS ehVhYGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B99s
(3GdPQjYI(B:(3L(B7(3,U(B24(3,Qbe(B160s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJaSjQ hYdhe GdbQBfs